O diálogo entre os gêneros capa de revista e reportagem de capa: um estudo à luz da Teoria da Estrutura Retórica (RST) e da Multimodalidade - Danúbia Aline Silva Sampaio (2018)
Based on the interface between Rhetorical Structure Theory (RST) Mann and Thompson (1988); Matthiessen and Thompson, (1988) Mann et al., (1992) and the Grammar of Visual Design (GVD) by Kress and Van Leeuwen (2006), this work has as its central aim theanalysis of the emergence of rhetorical relations in a multimodal approach, departing from the dialogue between two genres that are intrinsically related in magazines: the magazine coverand the cover story. We started from the hypothesis that the strong connection between these two genres allows for textual portions of the cover to combine with textual portions of the cover story and vice-versa. The combinations between parts of distinct texts, on the otherhand, promote the emergence of different rhetorical relations, which stands, according to this study, as one of the most key factors that constitute and characterize the dialogue between cover and report. Before investigating, however, the emergence of meaning relations betweenthe mentioned texts, before considering the connections between text and image, both cover and the cover story were examined separately. The particular investigation on the cover was guided by three perspectives of analysis: (1) analysis of the emergence of rhetorical relationsbetween the written parts of the text; (2) study of the central image from the categories of analysis presented by GVD; (3) analysis of emergence of rhetorical relations between written parts and images. The investigation on the macrostructure of covers was guided, on the otherhand, by two perspectives: (1) analysis on the emergence of rhetorical relations between written parts and (2) analysis on the emergence of rhetorical relations between written parts and images. Covers and reports were taken from a selected issue of each of the three mostprominent information magazines in Brasil: Veja, IstoÉ and Carta Capital. These weekly publications are characterized as opinion leaders and they circulate all national territory. The chosen issue also has as its main theme the matter of reducing criminal majority. From the analyses of emergence of rhetorical relations between distinct semiotic modes in the cover and in the cover story, we noticed that RST enabled us not only to identify simple relations between the elements composing the textual arrangement of those genres, but also to describe in a more elaborate manner how all parts from these texts are connected to each other,organized in the constitution of a complex structure. Specially, it was possible to identify and discuss, in a multimodal approach, how the emergence of rhetorical relations between texts works, indicating how these intertextual combinations serve the construction of the point ofview held by the company issuing the magazine, in regard to the approached theme in the examined issues.